Influence of breed, production system and fecundity on serum antioxidant profiles of goats reared in the tropical Island conditions - ALYETHODI, RAFEEQUE R; SUNDER, JAI; KARTHIK, S.; PERUMAL, P; BALA, P A; MUNISWAMY, K; DE, ARUN K; BHATTACHARYA, D (The Indian Journal of Animal Sciences, 2022)
The present study assessed the physiological antioxidant status of goats reared under the humid tropical island ecosystem of the Andaman and Nicobar Islands (ANI). From 2019 to 2020, 25 multiparous non-pregnant does with three to six kidding records maintained in the organized farm of Central Island Agricultural Institute (CIARI) and farmer’s field flocks from South Andaman district were selected for the study. Antioxidant markers such as total antioxidant capacity (TAC), superoxide dismutase (SOD), TG (Total glutathione) and catalase (CAT) were analyzed in blood serum with respect to rearing systems, breeds and level of fecundity. Correlation analyses of all dependent variables were performed using Pearson’s correlation. The endogenous antioxidant systems, viz. CAT, TG and SOD was non-significant with respect to rearing systems, breeds and fecundity. Similarly, TAC was non-significant among the breeds and with fecundity; however, semi-intensively managed goats showed significantly higher values than goats under the extensive condition. Correlation analysis showed that CAT was positively correlated with SOD and negatively correlated with TAC. TG showed no correlation with any of the studied antioxidants. Regression analysis of CAT as dependent variable and SOD and TAC as independent variables showed significance. It is concluded that values of antioxidant in the study can be considered as a baseline data for the ALG and other goat breeds of Andaman and Nicobar Islands and other islands or topographies with similar ecosystems for further studies.